Oral Health Complications in Type 2 Diabetes: A Hospital-Based Observational Study among Beneficiaries of Employees State Insurance in Puducherry, India - Palash Kumar Sanyal; Pramod Srirammohan; Sirshendu Chaudhuri (Indian Journal of Medical Specialities)
Background: Oral health evaluation is one aspect of diabetes care, that is usually not practised in majority of health care settings in India. Aims: To-identify the various complications related to oral health among Type 2 diabetics in a secondary care hospital in South India; and to identify the various determinants associated with it. Methods: In this cross-sectional study among the employees state insurance beneficiaries, we conveniently sampled the Type 2 diabetes patients attending the outpatient department for routine diabetic care and evaluated for some preidentified oral health conditions. Results: We recruited 124 participants, 76 (61.3%) males. The average duration of diabetes was 6.5 years (inter-quartile range-3–7 years). Gingivitis (n = 97, 78.2%) was the most common complication. Other important complications include-loss of functionality (n = 88, 71%), calculous (n = 87, 70.2%), and gingival recession (n = 56, 45.2%). In multivariate logistics regression modeling, young diabetics (adjusted odds ratio [AOR] −6.2; 95% confidence interval [CI] −2.2,17.6) and male populations (AOR − 2.6; 95% CI − 1.1, 6.0) were at higher risk of developing multiple complications. Conclusions: Diabetic population frequently suffers with oral complications. Health care professionals can include the importance of dental health care in the routine health education session for diabetics. In addition, clinicians can recommend dental evaluation to the diabetics apart from other clinical biochemical evaluation.